Fundamental of Entrepreneurship (ENT300) : Gifts and stationeries / Nur A’inaa Izzati Nazarihan … [et al.] - Nazarihan, Nur A’inaa Izzati; Jamel, Mohd Shafiq Aima; Pathe, Khuhaimy (2018)
Business opportunity means a situation that favours the entrepreneur to offer the products or services that other businesses do not offer or derive from. Business opportunity is not about just the current situation we could utilize, but also, we study and explore the business environment which is located in Kuching, our stationery store company and also the community of how their demands gives impact towards possible outcomes of the sale. Besides that, in screening of business opportunity, we also discuss about the legal issues, monopolistic power among the major stationary stores, how the level of competition is, the capital requirement and the risks behind the opportunities to start a stationery store itself.